Opening the s-triazine ring and biuret hydrolysis during conversion of atrazine by Frankia sp. strain EuI1c. (February 2017) - Rehan, Medhat; El Fadly, Gomaah; Farid, Mona; El sharkawy, Aml; Fränzle, Stefan; Ullrich, René; Kellner, Harald; Hofrichter, Martin
Abstract: Three genes have been identified through sequence analysis to encode putative AtzD/TrzD and AtzE enzymes and a TrzR transcriptional regulator via deduced amino acid sequences of functional AtzD/TrzD and/or AtzE published in the literature via a query sequence for homologues at the protein level using BLASTP. The operon was predicted to encode an s -triazine ring-opening amidohydrolase, TrzD (FraEuI1c_3137) and a GntR family transcriptional regulator, TrzR (FraEuI1c_3136), which may regulate the expression of ring-cleavage enzyme whereas the putative atzE (FraEuI1c_1007) gene encodes aspartyl/glutamyl-tRNA (Asn/Gln) amidotransferase subunit A in the course of s -triazine degradation by Frankia strain EuI1c. LC-MS analysis of Frankia sp EuI1c culture filtrates grown in the presence of atrazine or desethyl-desisopropylatrazine revealed a metabolite with a molecular ion (major peak) of m / z 102.7, which was identified as biuret. The trzD (FraEuI1c_3137) gene expression increased up to 4.7-fold in its abundance under 2 mM atrazine exposure when qRT-PCR was applied. Moreover, the mRNA level of the putative trzR (FraEuI1c_3136) gene that is proposed to regulate the gene function of FraEuI1c_3137 exhibited a dose-response and peaked at 2 mM atrazine with a 6.5 fold-increased mRNA level. The putative atzE (FraEuI1c_1007) mRNA level exhibited dose-respond and upregulated up to 10-fold change under the same stress dose.